Research on capacity region of Gaussian degraded relay broadcast channel - Ma Yingying (Journal of Shanghai Normal University (Natural Sciences), 2017)
Considering the relay broadcast channel (RBC),the transmitter communicates with two receivers with the assistance of a relay.Based on degradation orders among the relay and the receiver outputs,three types of physically degraded RBCs (PDRBCs) model are introduced and the Gaussian PDRBC channel capacity is determined.